2014
DOI: 10.1101/gad.250902.114
|View full text |Cite
|
Sign up to set email alerts
|

ATP-dependent chromatin remodeling shapes the long noncoding RNA landscape

Abstract: Long noncoding RNAs (lncRNAs) are pervasively transcribed across eukaryotic genomes, but functions of only a very small subset of them have been demonstrated. This has led to active debate about whether many of them have any biological functions. In addition, very few regulators of lncRNAs have been identified. We developed a novel genetic screen using reconstituted RNAi in Saccharomyces cerevisiae and systematically identified a large number of putative lncRNA repressors. Among them, we found that four highly… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

7
59
0

Year Published

2015
2015
2020
2020

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 49 publications
(66 citation statements)
references
References 60 publications
7
59
0
Order By: Relevance
“…Much like FACT, a chromatin remodeler that also reduces R-loop formation to enable replication fork progression through transcribed regions (Herrera-Moyano et al 2014), INO80C was reported to limit the abundance of spurious and unstable noncoding RNA transcripts (Alcid and Tsukiyama 2014). This may be related to the RNAPII eviction that we scored on HU.…”
Section: A Novel Role For Paf1c In Polymerase Evictionmentioning
confidence: 99%
See 1 more Smart Citation
“…Much like FACT, a chromatin remodeler that also reduces R-loop formation to enable replication fork progression through transcribed regions (Herrera-Moyano et al 2014), INO80C was reported to limit the abundance of spurious and unstable noncoding RNA transcripts (Alcid and Tsukiyama 2014). This may be related to the RNAPII eviction that we scored on HU.…”
Section: A Novel Role For Paf1c In Polymerase Evictionmentioning
confidence: 99%
“…INO80C maps to many transcription start sites in budding yeast yet also contributes to DSB repair and replication fork restart following removal of hydroxyurea (HU) (Gerhold et al 2015). Interestingly, INO80C can down-regulate transcription by repressing short-lived noncoding RNA at intergenic sites (Alcid and Tsukiyama 2014), possibly by restricting accessibility for RNA polymerase (Xue et al 2015).…”
mentioning
confidence: 99%
“…The INO80 complex has demonstrated roles in transcription (7)(8)(9), replication (10)(11)(12), DNA damage responses (13)(14)(15)(16), telomere regulation (17), and mitotic stability (18,19). These studies exemplify the functional diversity of the INO80 complex in different pathways (20).…”
mentioning
confidence: 97%
“…43 Therefore, the highly conserved ATP-dependent chromatin-remodeling factors may serve as global lncRNA repressors. 43 The repression of antisense lncRNAs may be a common mechanism of mRNA regulation. This view is consistent with the observation that Brg1 represses the expression of Mhrt, which is antisense to Myh7, to promote the expression of Myh7 mRNA in pathologically stressed hearts.…”
Section: Lncrna Transcription Can Be Controlled By Atp-dependent Chromentioning
confidence: 99%
“…43 These chromatinremodeling factors repress over 250 antisense lncRNAs (chromatin remodelingrepressed antisense transcripts or CRRATs) to maintain normal expression of mRNA transcripts that overlap with those antisense lncRNAs. 43 Therefore, the highly conserved ATP-dependent chromatin-remodeling factors may serve as global lncRNA repressors. 43 The repression of antisense lncRNAs may be a common mechanism of mRNA regulation.…”
Section: Lncrna Transcription Can Be Controlled By Atp-dependent Chromentioning
confidence: 99%